Meningkatkan Profesionalitas Kerja Dengan Pemahaman Etika Profesi Dalam Dunia Bisnis - H Suhada; Hendra Kusumah; Muhammad Rizki Fadlan Nullah (UNIVERSITAS RAHARJA, 2024)
In becoming a professional at his job, it is necessary to instill and apply an understanding of professional ethics. Professional ethics is a very important aspect in carrying out business activities. Professional ethics can affect a company's image, consumer trust, and relationships with business partners. Professional ethics must be considered more to be able to face all challenges in the business world. Professional ethics can help companies to maintain a good image and reputation in the eyes of the public and improve employee professionalism. In the research conducted by the researcher this time, it is a qualitative research with data collection methods through literature study methods via the internet. The purpose of this study is to find out how important professional ethics are in improving one's professionalism in running a business. This research can also contribute to the development of science and business practice in Indonesia, especially in strengthening aspects of professional ethics in business activities. Thus, this research is expected to provide a better understanding of the importance of professional ethics in business activities as well as provide solutions and recommendations to improve work professionalism by applying good professional ethics in business activities in Indonesia.